Can a clinical placement influence stigma? An analysis of measures of social distance. (September 2016) - Moxham, Lorna; Taylor, Ellie; Patterson, Christopher; Perlman, Dana; Brighton, Renee; Sumskis, Susan; Keough, Emily; Heffernan, Tim
Abstract: Background: The way people who experience mental illness are perceived by health care professionals, which often includes stigmatising attitudes, can have a significant impact on treatment outcomes and on their quality of life. Objective: To determine whether stigma towards people with mental illness varied for undergraduate nursing students who attended a non-traditional clinical placement called Recovery Camp compared to students who attended a 'typical' mental health clinical placement. Design: Quasi-experimental. Participants: Seventy-nine third-year nursing students were surveyed; n  = 40 attended Recovery Camp (intervention), n  = 39 (comparison group) attended a 'typical' mental health clinical placement. Methods: All students completed the Social Distance Scale (SDS) pre- and post-placement and at three-month follow-up. Data analysis consisted of a one-way repeated measures analysis of variance (ANOVA) exploring parameter estimates between group scores across three time points. Two secondary repeated measures ANOVAs were performed to demonstrate the differences in SDS scores for each group across time. Pairwise comparisons demonstrated the differences between time intervals. Results: A statistically significant difference in ratings of stigma between the intervention group and the comparison group existed. Parameter estimates revealed that stigma ratings for the intervention group were significantly reduced post-placement and remained consistently low at three-month follow-up. There was no significant difference in ratings of stigma for the comparison group over time. Conclusions: Students who attended Recovery Camp reported significant decreases in stigma towards people with a mental illness over time, compared to the typical placement group. Findings suggest that a therapeutic recreation based clinical placement was more successful in reducing stigma regarding mental illness in undergraduate nursing students compared to those who attended typical mental health clinical placements. Highlights: It is well known that stigma has detrimental effects on the wellbeing of people with mental health issues. Strategies that may positively address stigma, which are also relevant to nursing students, include education and familiarisation. Nursing students who attended a non-traditional clinical placement reported decreases in stigma towards people with a mental illness.